A male infant had subdural effusion and paroxysmal supraventricular tachycardia during the febrile episode of Kawasaki disease: a case report and literature review. Issue 1 (December 2016) - Chou, Chia-Pei; Lin, I-Chun; Kuo, Kuang-Che
Abstract Background Kawasaki disease is an acute, febrile, self-limiting, inflammatory systemic vasculitis seen in early childhood, most commonly in those below 5 years of age. In Kawasaki disease, the coronary arteries are most commonly affected, which may lead to asymptomatic coronary artery ectasia or formation of an aneurysm. Paroxysmal supraventricular tachycardia(PSVT) is a severe and rare cardiovascular complication of Kawasaki disease. A case of Kawasaki disease presenting with unusual findings, including subdural effusion and PSVT is reported. Case presentation This is a 4-month-10-day-old boy presents with anterior fontanelle bulging and moderate bilateral subdural effusion at the acute stage of Kawasaki disease and PSVT at the subacute stage of Kawasaki disease. The subdural effusion was resolution after intravenous immunoglobulin(IVIG) administration. And the PSVT was subsided after administered 3 doses of adenosine, 1 dose of amiodarone loading and Propranolol twice per day use. At 1-year follow-up has made a complete recovery with no arrhythmia episodes, developmental effects or abnormal neurologic findings. Conclusion Subdural effusion in the acute stage of Kawasaki disease may be an inflammatory response. It may resolves spontaneously after anti-inflammatory treatment such as IVIG infusion. PSVT is a severe cardiovascular complication of Kawasaki disease. In those who taking aspirin, we need to carefully observe the heart rhythm and PSVT side effects, especially in the first month.